Phospholipase C-ζ-induced Ca2+ oscillations cause coincident cytoplasmic movements in human oocytes that failed to fertilize after intracytoplasmic sperm injection. - Swann, K; Windsor, S; Campbell, K; Elgmati, K; Nomikos, M; Zernicka-Goetz, M; Amso, N; Lai, F; Thomas, A; Graham, C (2012)
OBJECTIVE: To evaluate the imaging of cytoplasmic movements in human oocytes as a potential method to monitor the pattern of Ca(2+) oscillations during activation. DESIGN: Test of a laboratory technique. SETTING: University medical school research laboratory. PATIENT(S): Donated unfertilized human oocytes from intracytoplasmic sperm injection (ICSI) cycles. INTERVENTION(S): Microinjection of oocytes with phospholipase C (PLC) zeta (ζ) cRNA and a Ca(2+)-sensitive fluorescent dye. MAIN OUTCOME MEASURE(S): Simultaneous detection of oocyte cytoplasmic movements using particle image velocimetry (PIV) and of Ca(2+) oscillations using a Ca(2+)-sensitive fluorescent dye. RESULT(S): Microinjection of PLCζ cRNA into human oocytes that had failed to fertilize after ICSI resulted in the appearance of prolonged Ca(2+) oscillations. Each transient Ca(2+) concentration change was accompanied by a small coordinated movement of the cytoplasm that could be detected using PIV analysis. CONCLUSION(S): The occurrence and frequency of cytoplasmic Ca(2+) oscillations, a critical parameter in activating human zygotes, can be monitored by PIV analysis of cytoplasmic movements. This simple method provides a novel, noninvasive approach to determine in real time the occurrence and frequency of Ca(2+) oscillations in human zygotes.